Down-regulation of the Sucrose Transporter CsSUT1 Causes Male Sterility by Altering Carbohydrate Supply. Issue 2 (9th April 2019) - Sun, Lulu; Sui, Xiaolei; Lucas, William J.; Li, Yaxin; Feng, Sheng; Ma, Si; Fan, Jingwei; Gao, Lihong; Zhang, Zhenxian
Abstract : CsSUT1 downregulation induces male sterility in cucumber by altering carbohydrate supply, and potentially auxin signaling, suggesting a strategy for bioengineering male sterility in crop plants. Abstract: In plants, male sterility is an important agronomic trait, especially in hybrid crop production. Many factors are known to affect crop male sterility, but it remains unclear whether Suc transporters (SUTs) participate directly in this process. Here, we identified and functionally characterized the cucumber ( Cucumis sativus ) CsSUT1, a typical plasma membrane-localized energy-dependent high-affinity Suc-H + symporter. CsSUT1 is expressed in male flowers and encodes a protein that is localized primarily in the tapetum, pollen, and companion cells of the phloem of sepals, petals, filaments, and pedicel. The male flowers of CsSUT1 -RNA interference (RNAi) lines exhibited a decrease in Suc, hexose, and starch content, relative to those of the wild type, during the later stages of male flower development, a finding that was highly associated with male sterility. Transcriptomic analysis revealed that numerous genes associated with sugar metabolism, transport, and signaling, as well as with auxin signaling, were down-regulated, whereas most myeloblastosis ( MYB ) transcription factor genes were up-regulated in these CsSUT1 -RNAi lines relative to wild type. Our findings demonstrate that male sterility can be induced by RNAi-mediated down-regulation of CsSUT1 expression, through the resultant perturbation in carbohydrate delivery and subsequent alteration in sugar and hormone signaling and up-regulation of specific MYB transcription factors. This knowledge provides a new approach for bioengineering male sterility in crop plants.